Drawing from nature as a factor in the development of creative imagination of schoolchildren in the process of artistic activity - L.F. Eyvas (Academy of Cognitive and Natural Sciences, 2006)
Influencing of painting is explored from nature on development of creative imagination of shoolbays in the conditions of educational lesson and groups of the decoratively-applied creation. The way's of surmounting obstacles of graphic activity are determined (thematic and decoratively drawing).